Issues and dilemmas of biotechnology : a reference guide - Schacter, Bernice, 1943-2008 (Greenwood Press, 1999)
Recent advances in biotechnology in areas as diverse as agriculture, the environment, food, and healthcare have led to much debate and media attention. This unique reference source for advanced high school students and teachers explores the science behind these new technologies and examines the stakeholders and their stakes in the various debates. The author presents views of scientists, doctors, insurance companies, and big businesses, among others, on such issues as genetic testing, patenting of human gene sequences, cloning, and genetically engineered food.